The Contribution of Alexandru Ioan Cuza University of Iai to the Increase of the Economic Activity Rate in the North Eastern Region and in Romania - Alexandru Cristian Fotea; Teodor Lucian Moga (CES Working Papers, 2011)
Over the past decades, knowledge, science and innovation have become the most important pillars on which the economic development is based. At the same time, the regions are considered to be the new poles of economic growth. In this context, universities are expected to expand their classic role to a leading actor in regional economic development. This paper focuses on how “Alexandru Ioan Cuza University” of Iai, the oldest and one of the most prestigious universities in Romania, contributes to this process, quantifying its indirect contribution to the generation of human capital, to the increase of the economic activity rate in the North Eastern Region and in Romania.
Keywords: O15; 330; economic activity rate; university; regional economic development; human capital Romania